Field screening of chickpea genotypes against pod borer - Hossain, MD Altaf (Bangladesh Journal of Agricultural Research, 2009)
DOI: 10.3329/bjar.v34i3.3978 Bangladesh J. Agril. Res. 34(3) : 517-521, September 2009